04.04 Suramin protects against osteoarthritis by increasing tissue inhibitor of matrix metalloproteinase-3 and glycosaminoglycans in the articular cartilage. (1st March 2017) - Guns, Laura-An; Kvasnytsia, Maryna; Kerckhofs, Greet; Vandooren, Jennifer; Martens, Erik; Opdenakker, Ghislain; Lories, Rik J; Cailotto, Frédéric
Abstract : Purpose: Drug repositioning is a recent pharmaceutical strategy to discover new uses for market-approved drugs, with known safety profiles that can provide quick transition from the laboratory bench to bedside. Here, we investigate the influence of suramin, a polysulfonated compound that has been used in vitro to isolate tissue inhibitor of metalloproteinase (TIMP)−3 from the rat uterus. We therefore hypothesised that suramin may protect articular cartilage against osteoarthritis, by decreasing the catabolic action of tissue destructive enzymes such as matrix metalloproteinases (MMPs) and ADAMTS (A disintegrin and metalloproteinase with thrombospondin motifs) through increasing TIMP3 levels in the cartilage matrix. Methods: We cultured differentiating ATDC5 mouse chondroprogenitor cell line in micromasses, and freshly-isolated human articular chondrocytes (hAC) in pellets, each at 200.000 cells/10 µl, in the presence or absence of 10 µM suramin. ATDC5s were differentiated 14 days (proliferation) in DMEM/F12 with insulin-transferrin-sodium selenite (ITS), and then 7 days (hypertrophy) in α-MEM with ITS, β-glycerophosphate and ascorbic acid. Readouts included analyses of extracellular matrix components (dimethylmethylene blue assay for sulfated glycosaminoglycan (sGAG) content, and histology), MMPs- and ADAMTS-induced aggrecan neo-epitopes (VDIPEN and NITEGE, by immunostaining) and phenotypic markers (quantitative PCR). We assessed the effects of suramin in vivo using the papain-induced model of osteoarthritis in C57BL/6 with or without a single intra-articular injection of 1 mg suramin. Cartilage damage was analysed by histology (OARSI scoring), and by Hexabrix contrast-enhanced nanofocus computed tomography, thereby quantifying cartilage volume. Results: In ATDC5 and hAC, TIMP-3 protein levels were increased. Presence of VDIPEN and NITEGE were decreased, thus sGAG content was increased. Noteworthy gene expression levels of phenotypic markers remained unaffected, suggesting a post-translational effect of suramin. Knees from Papain-triggered osteoarthritis in animals treated with suramin showed increased TIMP-3 and decreased VDIPEN and NITEGE levels. This potential protective mechanism effectively resulted in a decreased damage outcome and an increased cartilage volume. Conclusion: Our data suggest that suramin has a protective effect by increasing the amount of TIMP3 in the articular cartilage, leading to higher sGAG levels. Therefore, suramin is a new potential osteoarthritic disease-modifying agent that appears to act specifically within the cartilage matrix.